Virtualization: A Survey on Concepts, Taxonomy and Associated Security Issues - Sahoo, Jyotiprakash; Mohapatra, Subasish; Lath, Radha (2010 Second International Conference on Computer and Network Technology, 2010)
Virtualization is a term that refers to the abstraction of computer resources. The purpose of virtual computing environment is to improve resource utilization by providing a unified integrated operating platform for users and applications based on aggregation of heterogeneous and autonomous resources. More recently, virtualization at all levels (system, storage, and network) became important again as a way to improve system security, reliability and availability, reduce costs, and provide greater flexibility. This paper explains the basics of system virtualization and addresses pros and cons of virtualization along with taxonomy and challenges.